Development of potentiometric equipment for the identification of altered dry-cured hams: A preliminary study. (August 2015) - Girón, Joel; Gil-Sánchez, Luís; García-Breijo, Eduardo; Jesús Pagán, Mª.; Barat, José M.; Grau, Raúl
Abstract: Microbiological contamination in dry-cured ham can occur in the early stages of the process, a large number of microorganisms involved in spoilage can produce alterations in the product. These include non-common odours, which are detected at the end of the process by a procedure called "cala", consisting of a sharp instrument punctured in every ham; this is smelled by an expert taster, who classifies hams as good and altered hams. An electronic device would be suitable for this process given the large amount of hams. The present research aims to develop objective equipment based on the potentiometry technique that identifies altered hams. A probe was developed, containing silver, nickel and copper electrodes, and was employed to classify altered and unaltered hams prior to classification by a tester. The results shown lower Ag and higher Cu potential values for altered hams. The differences in potentiometric response reveal a classification model, although further studies are required to obtain a reliable classification model. Highlights: Hams quality was evaluated with a potentiometric sensor. Evaluation process called "cala" is done at the end of the curing lap. "Cala" is a subjective method that could be turned into an objective method. The potentiometric sensor was able to differentiate between normal and altered hams. The silver electrode showed the best performance to distinguish between hams.